2002
DOI: 10.4049/jimmunol.169.5.2781
|View full text |Cite
|
Sign up to set email alerts
|

Activation of APCs Through CD40 or Toll-Like Receptor 9 Overcomes Tolerance and Precipitates Autoimmune Disease

Abstract: Some autoreactive T cells normally escape thymic selection and persist in the periphery. This is true of myelin-reactive CD4+ T cells, the effectors of experimental autoimmune encephalomyelitis (EAE) in laboratory animals and the presumed mediators of multiple sclerosis in humans. Nonetheless, most individuals do not succumb to autoimmune disease. There is growing evidence that while peripheral APCs stimulate immune responses against foreign Ags in the setting of tissue destruction and “danger,” they actually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 67 publications
4
89
2
2
Order By: Relevance
“…Rather it appears to allow the T cells to persist in a non-tolerant/non-immune state such that they can be subsequently activated by Ag in CFA. To further highlight differences in soluble and insoluble "adjuvants", CpG oligonucleotides in an IFA depot have been shown to substitute for CFA in the induction of encephalitogenic Th1 cells [28,30]. We found that CpG had no effect on tolerance induced with soluble peptide (data not shown).…”
Section: Cd40-cd154 Signalling Is Not Required For the Induction Of Tmentioning
confidence: 81%
See 1 more Smart Citation
“…Rather it appears to allow the T cells to persist in a non-tolerant/non-immune state such that they can be subsequently activated by Ag in CFA. To further highlight differences in soluble and insoluble "adjuvants", CpG oligonucleotides in an IFA depot have been shown to substitute for CFA in the induction of encephalitogenic Th1 cells [28,30]. We found that CpG had no effect on tolerance induced with soluble peptide (data not shown).…”
Section: Cd40-cd154 Signalling Is Not Required For the Induction Of Tmentioning
confidence: 81%
“…the antibody could provoke a productive immune response without subsequent immunization [8][9][10][11]. However, these previous studies have used an immunization protocol that gave a sustained Ag stimulus (peptide in IFA for example) [10,28]. Giving soluble peptide as we have here does not replicate this sustained Ag availability, the peptide being cleared from the system rapidly [29].…”
Section: Cd40-cd154 Signalling Is Not Required For the Induction Of Tmentioning
confidence: 98%
“…The mechanisms by which autoimmunity is triggered are not fully understood, but DCs and TLRs are likely to play a role in this process. Recently, Ichikawa and colleagues (30) and Waldner and associates (31) provided a conceptual framework demonstrating that TLRs are key molecules for the breakthrough of tolerance. Our data show that triggering different TLRs at the same time resulted in marked synergy with respect to the production of proinflammatory mediators, indicating that simultaneous stimulation of different TLR pathways facilitates an environment in which the breakthrough of tolerance is likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous ligands are released upon normal cell turnover and stressful events and are likely to be abundant in the synovial compartment. The pivotal role of endogenous ligands was substantiated by the finding that such signals lead to primary immune responses under conditions of cell stress and precipitate autoimmunity in the presence of self antigens (28)(29)(30)(31). Therefore, endogenous ligands are considered to be natural initiators of autoimmunity.…”
mentioning
confidence: 99%
“…These results were consistent with previous studies that suggested that T cells induced by antigen:IFA may be in a transitional state and retain the ability to differentiate into pathogenic effectors under Th1-polarizing conditions. 56,67,68 Our data also suggested that antigen:IFA-induced tolerance to myocarditis is a dynamic process and can be broken by strong inflammatory stimuli produced by APCs. 68 -70 After expo- sure to high doses of exogenous IL-12, S2-16:IFA-induced cells produced increased IFN-␥ but not IL-10 in response to S2-16.…”
Section: Discussionmentioning
confidence: 73%